Uma contribuição ao estudo da exclusão na educação como causa da concentração de renda no Brasil: aspectos teóricos e evidências empíricas - Vasconcellos, Lígia Maria de (1998)
This disserlation analyses the educational policy as cause of an exclusionary process, which difficults the access of the poor to education and to its future benefits, with negative effects on the income distribution. It is argued that the brazilian educational policy shows these characteristics and evidence is presented on distribution of income and education for Brazil and the world.